2019
DOI: 10.1063/1.5111643
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of ionic liquids with symmetric and asymmetric fluorinated anions

Abstract: Ionic liquids (ILs) with relatively low viscosities and broad windows of electrochemical stability are often constructed by pairing asymmetric cations with bisfluorosulfonylimide (FSI−) or bistriflimide (NTf2 −) anions. In this work, we systematically studied the structures of ILs with these anions and related perfluorobis-sulfonylimide anions with asymmetry and/or longer chains: (fluorosulfonyl)(trifluoromethylsulfonyl)imide (BSI0,1−), bis(pentafluoroethylsulfonyl)imide (BETI−), and (trifluoromethylsulfonyl) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 96 publications
0
25
0
Order By: Relevance
“…What we mean by this is that whereas it is easy to get transport properties wrong (sometimes very wrong) for ILs, it is hard for a reasonable force field to not show the three typical characteristics of an IL: which are polar–apolar alternation [the so-called prepeak or first sharp diffraction peak (FSDP)], charge alternation, and adjacency correlations. 116 126 Each of these features appears in a specific q -range, as shown in Figure 5 (left). 119 , 127 134 Instead, structural properties of molten salts including coordination numbers and intermediate range order appear to be quite sensitive to the model and, as opposed to the case for ILs, it is very easy to get these wrong.…”
Section: Resultsmentioning
confidence: 99%
“…What we mean by this is that whereas it is easy to get transport properties wrong (sometimes very wrong) for ILs, it is hard for a reasonable force field to not show the three typical characteristics of an IL: which are polar–apolar alternation [the so-called prepeak or first sharp diffraction peak (FSDP)], charge alternation, and adjacency correlations. 116 126 Each of these features appears in a specific q -range, as shown in Figure 5 (left). 119 , 127 134 Instead, structural properties of molten salts including coordination numbers and intermediate range order appear to be quite sensitive to the model and, as opposed to the case for ILs, it is very easy to get these wrong.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, theoretical chemical calculations of cation-anion energy were done in order to support experimental results. The advantages of using those DILs are due to their important thermal stability in comparison with their asymmetric counterparts [11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In this combined experimental (steady‐state and time‐resolved fluorescence quenching) and theoretical (MD simulations) approach it is shown that spherical diffusion‐reaction models are not perfectly suited for reactions in RTILs, but that contact pairs serve to gate the electron transfer. These findings have been intensified in a subsequent study where it is shown that depending on the imidazolium cation the size of the anion led to percolation aggregation influencing physicochemical properties such as conductivity [64] …”
Section: Resultsmentioning
confidence: 99%